Measurement and Analysis of Acoustic Backscatter Value for Bottom Classification of waters Tidung Island - M Hasbi Sidqi Alajuri; Henry M Manik; Sri Pujiyati (Journal of Applied Geospatial Information, 2021)
Sediment in a water has an important role for organisms, namely as a habitat, a place for foraging for food, and a place for spawning. These sediment can affect the composition of organisms in the water. The purpose of this study is to calculate the value of acoustic backscatter for the classification of the bottom of the water and to see the effect of sediment grain size on the backscatter value obtained from a single beam acoustic instrument. Data collection was carried out from 10 to 12 June 2021 in the water of Tidung Island, Seribu Islands, using the SIMRAD EK-15 single beam, single frequency 200 kHz instrument. Sediment sampling was carried out at 13 stations. The results showed that the waters of Tidung Island were dominated by muddy substrate which was classified based on the Surface Backscattering Strength (SS) value. Meanwhile, the grain size of the sediment affects the SVb value, where the large the grain size of the bottom sediment, the SVb value will be higher. The higher SVb value the SS value will be higher. Keywords: Bottom Classification, Acoustic Backscatter, Tidung Island